Governance configurations of coordination in municipal health promotion: insights from an egocentric network analysis - Hanna Richter; Tatiana Mamontova; Lisa Kühne (BMC Health Services Research, 2026)
Abstract Background Municipal health promotion requires coordination across organizational and sectoral boundaries. Fragmented responsibilities, strong organizational autonomy and limited formal authority can make sustained cross-sectoral coordination challenging. Although research on Health in All Policies and governance capacity has highlighted the organizational conditions necessary for coordination, little is known about how coordination functions are embedded within municipal governance networks. This study examines the structural conditions that shape cross-sectoral coordination in municipal health promotion. Methods Egocentric social network analysis was used to map the professional networks of 14 health professionals working in primary schools and neighborhood settings in a single German municipality. Data were collected through semi-structured interviews combined with structured network elicitation, capturing 662 individuals, their reported interconnections and organizational attributes. Network measures of structural integration, modular differentiation, local cohesion and relational dependency were combined with modularity analysis and ego-removal comparisons. Qualitative interview data contextualized the structural findings and supported the functional interpretation of network modules. Results The networks varied considerably in terms of the structural organization of cross-sectoral coordination. Modularity analysis revealed the following recurring governance domains: education; neighborhoods and social spaces; professional coordination and peer networks. The combined analysis identified three governance configurations. In ego-dependent integration, internally cohesive network areas remained intact after the removal of the ego, but lost connections to other areas. In substitutable coordination, connectivity persisted through alternative individual or collective coordination hubs or relational pathways. In distributed integration, cross-module connectivity was supported by multiple relationships and remained largely intact even without the focal actor. Therefore, network connectedness and local cohesion alone did not determine how strongly coordination depended on individual brokers. Conclusion Municipal coordination capacity depends not only on coordinating professionals and their resources, but also on how brokerage and cross-sectoral relationships are structurally embedded in governance networks. Therefore, strengthening municipal health promotion requires the establishment of adequately resourced and formally supported coordination roles, as well as investment in collective coordination arenas, alternative coordination pathways, and direct cross-sectoral relationships. Recognizing network work as a continuous strategic function can help to create governance structures that are less vulnerable to the loss of individual actors.